2018
DOI: 10.1111/cas.13486
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of “clinical sequencing” in cancer genome medicine in Japan

Takashi Kohno

Abstract: In oncology, actionable mutations (alterations) in cancer‐associated genes are critical in terms of the selection of therapeutic approaches. Next‐generation sequencing of tumor sample DNA (ie, clinical sequencing) can guide clinical management by providing diagnostic or prognostic data, and facilitating the identification of potential treatment regimens, such as molecular‐targeted and immune checkpoint blockade therapies. In the USA, a variety of tumor‐profiling multiplex gene panels have been developed and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…A recent prospective cohort study in the USA revealed that only 11% of patients receiving the MSK‐IMPACT gene panel test were subsequently enrolled on genomically matched clinical trials . The gaps between the number of patients with actionable mutations and those receiving genomically matched therapy indicate the need to develop drugs targeting new genes covering not only druggable kinase genes but also nonkinase genes such as epigenomic and transcriptional regulator genes, which are often mutated in a variety of tumors . Developing drugs that target such currently undruggable molecules will be of great help.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent prospective cohort study in the USA revealed that only 11% of patients receiving the MSK‐IMPACT gene panel test were subsequently enrolled on genomically matched clinical trials . The gaps between the number of patients with actionable mutations and those receiving genomically matched therapy indicate the need to develop drugs targeting new genes covering not only druggable kinase genes but also nonkinase genes such as epigenomic and transcriptional regulator genes, which are often mutated in a variety of tumors . Developing drugs that target such currently undruggable molecules will be of great help.…”
Section: Discussionmentioning
confidence: 99%
“…Gene panel tests have not yet been implemented in routine oncological practice in Japan; ie, they have not been reimbursed by the national insurance system run by the Japanese Ministry of Health, Labor, and Welfare (MHLW) . However, several academic institutions have examined the feasibility and utility of gene panel tests, and 3 major Japanese cancer‐related societies (the Japanese Society of Medical Oncology, the Japanese Society of Clinical Oncology, and the Japanese Cancer Association) have issued consensus clinical practice guidance for NGS‐based cancer tests (the Consensus Clinical Practice Guidelines for Next Generation Sequencing in Cancer Diagnosis and Treatment [Edition 1.0]; http://www.jsmo.or.jp/about/kanko.html#guideline) . Therefore, it is likely that implementation of gene panel tests in Japan will happen soon.…”
Section: Introductionmentioning
confidence: 99%
“…The MYB‐NFIB fusion results in an increased expression of the protein Myb . Myb is important for the growth of multiple solid tumors, and MYB protein overexpression in ACC is associated with a more aggressive clinical course . For example, Mitani et al reported that the level of MYB expression in identical histological subtypes of ACC is associated with a shorter survival time.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, the American Medical Association introduced specific NGS panel codes, and we calculated the overall reimbursement rate by dividing the total sum of obtained payments through the total sum of charges using CMS values as a reference. For comparison of our reimbursement rates with local, national, and international rates, we reviewed reimbursement data from selected publications [28][29][30][31][32][33][34][35][36].…”
Section: Economic Analysismentioning
confidence: 99%
See 1 more Smart Citation